An Improved, Scalable Synthesis of the Selective Serotonin 2A Receptor Agonist 25CN-NBOH - Märcher-Rørsted, Emil; Nykodemová, Jitka; Kristensen, Jesper L. (SynOpen, 2021)
4-{2-[(2-hydroxybenzyl)amino]ethyl}-2,5-dimethoxybenzonitrile (25CN-NBOH) was first reported as a potent and highly selective serotonin 2A receptor (5-HT2AR) agonist in 2014. The compound has since found extensive use as a pharmacological tool in a variety of in vivo and in vitro studies. In the present study, we present an improved and scalable synthesis of 25CN-NBOH making this compound readily available to the scientific community.
Keywords: amines; benzylation; chemoselectivity; medicinal chemistry; condensation